Teacher Education and Foreign Language Teacher Professionalism in The 21st Century - Tütüniş, Birsen; Yalman, Duygu (Hacettepe Üniversitesi, 2020)
The quality of foreign language teaching improves so long as foreign language teacher education quality is increased. However, it is not easy to measure the quality of Foreign Language Teacher Education (FLTE) programmes due to the factors related not to the programme but to the learner variables. It has been proved by the research (Sutton Trust 2011) that improving teacher effectiveness has a great impact on learner outcomes. In the 21st century, Professional development of the teacher has gained importance due to the precedence given to the learners. For this reason frameworks and models have been proposed to enhance the quality of teacher education (i.e. NIE, VSK Model, 2009).This paper focuses on Teacher Education programme models and the criteria put forward by these models. A comparison of Turkish and other FLTE programmes is given in order to bring clarity to the concept of professionalism. The small-scale research results conducted in Turkish context (n81) to check upon foreign language teacher knowledge and beliefs on efficacy and professionalism are also displayed.
Keywords: Foreign Language Teacher Education (FLTE); English Language Teaching (ELT); Teacher Education (TE); Values; Skills and Knowledge (VSK)